Assessment of p otential socio-economic imp acts of the West Sumatra -Riau toll road: a comp rehensive study for the city of Payakumbuh, Indonesia - Rahmat Eka Putra; Fajri Adrianto; Hendra Lukito; Sri Maryati; Robby Hafanos; Dasatry Dwi Ramadona (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2023)
The West Sumatra - Riau toll road is expected to generate a favourable influence on the local economy, thereby enhancing the overall wellbeing of society. However, this progress does not eliminate some of the potential negative impacts, because the construction of toll roads will divert some of the public's transportation movements, thereby posing a threat to business activities along the diverted transportation routes. To anticipate these potential impacts, it is important to conduct a study that focuses on anticipating the potential socio-economic impacts of the construction of the West Sumatra – Riau toll road. A Focus Group Discussion was conducted with delegates from several Payakumbuh Municipal Government. A total of nineteen participants, comprising ten males and nine females, participated in the focus group discussion. The discussion remarks were methodically categorised and analysed. The study findings elucidate many potential ramifications of the construction of the West Sumatra - Riau toll road on Payakumbuh City, as well as proposed measures that might be implemented to mitigate these ramifications. The research findings can serve as a foundation for developing a regional development strategy for Payakumbuh City. The objective is to optimise the effects of toll road construction on the social and economic well-being of the community, ensuring equitable and balanced outcomes.